Nuclear Realism global polotical thought during the thermonuclear revolution - Munster, Rens van 1977-; Sylvest, Casper (New international relations, 2016)
This book brings out an important, oppositional and resolutely global strand of political thought that combines realist insights about nuclear weapons with radical proposals for social and political transformation as the only escape from a profoundly endangered planet